Integrating anthropic factors into wildcat Felis silvestris conservation in Southern Iberia landscapes - ferreira, joaquim Pedro (2010)
Tese de doutoramento, Biologia (Biologia da Conservação), Universidade de Lisboa, Faculdade de Ciências, 2010